IMPROVEMENT IN THE DIAGNOSIS OF CHRONIC PERIODONTITIS IN CHILDREN - Nilufar I. Abdullaeva (Central Asian Journal of Medicine, 2024)
The clinical development of periodontitis in children differs in many ways from the similar pathological process in adults. This is due to the fact that these processes take place in morphologically and functionally immature tissues, which are unable to respond adequately to the causative factors. Despite the fact that destructive periodontitis is less common, children are more likely to develop severe forms of periodontitis than adults. Chronic periodontitis is the cause of acute inflammatory processes in the maxillofacial region (abscess, phlegmon, lymphadenitis) in 85-98% of cases and is a manifestation of systemic and other dental diseases.